The Secular in South, East, and Southeast Asia - Dean, Kenneth; van der Veer, Peter; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This innovative edited collection provides a comprehensive analysis of modern secularism across Asia which contests and expands prevailing accounts that have predominantly focused on the West. Its authors highlight that terms like 'secular', 'secularization', and 'secularism' do not carry the same meanings in the very different historical and cultural contexts of Asia. Critiquing Charles Taylor's account of secularism, this book examines what travelled and what not in 'the imperial encounter' between Western secular modernity and other traditions outside of the West. Throughout the book, state responses to religion at different points in Chinese and South-East Asian history are carefully considered, providing a nuanced and in-depth understanding of post-secular strategies and relations in these areas. Particular attention is given to Catholicism in the Philippines, Vietnam, and Singapore, and Hinduism and Chinese religion in Malaysia, Singapore, and India. This theoretically engaged work will appeal to students and scholars of Asian studies, anthropology, religious studies, history, sociology, and political science.
Chapter 1: Introduction; Kenneth Dean and Peter van der Veer -- Chapter 2: Asian Catholicism, Interreligious Colonial Encounters and Dynamics of Secularism in Asia; Jose Casanova -- Chapter 3: The Secular in India and China; Peter van der Veer -- Chapter 4: Spirit Mediums and Secular/Religious Divides in Singapore; Kenneth Dean -- Chapter 5: Secularization, Sacralization and Subject Formation in Modern China; David A. Palmer and Fabian Winiger -- Chapter 6: The Third Globalization of Catholicism in Greater China; Richard Madsen -- Chapter 7: "Folk Belief," Cultural Turn of Secular Governance and Shifting Religious Landscape in Contemporary China; Xiaoxuan Wang -- Chapter 8: The Roles of Secular States in the Development of Contemporary Chinese Buddhism: A Cross-Strait Perspective on Buddhist Nunneries; Tzu-Lung Chiu -- Chapter 9: Communist Ideology, Secularity, and Reenchantment Challenges for the Catholic Church in Vietnam, 1954-2015; Peter C. Phan -- Chapter 10: The Uncle Ho Religion inVietnam; Tam T.T. Ngo -- Chapter 11: From Secularism to Popular Progressiveness: Popular Religion and the Creation of Telangana Regionalism; Stefan Binder -- Chapter 12: Adjudicating the Sacred: The Fates of 'Native' Religious Endowments in India and Hong Kong; Leilah Vevaina -- Chapter 13: Secularism and Religious Modernity in Sri Lanka & Singapore: Transregional Revivalism Considered; Neena Mahadev.
Keywords: Religion and sociology; Ethnology; Ethnology -- Asia; Culture; Religion and politics; Sociology of Religion; Sociocultural Anthropology; Asian Culture; Politics and Religion